Effect of growing seasons on agronomic and functional traits of tunisian potato genotypes - Ilahy, Riadh; Tlili, Imen; R Him, Thouraya; Homa, Fozia; Lenucci, Marcello Salvatore; Khamassy, Nouri (Journal of Postharvest Technology, 2019)
This study investigates the main agronomic attributes (average tuber weight, soluble solids and dry matter) and the functional quality (total carotenoids,  total phenols, flavonoids and total vitamin C) as well as the hydrophilic and lipophilic antioxidant activities (HAA and LAA) of potato genotypes  consisting of six new clones (SLN, ELD, SYN, BDA, NMA, UNV) and the cultivar Spunta grown under a coastal location for the Rear Cropping Season  (RCS) and an inland or highland location for the New Cropping Season (NCS) commonly known as the fifth season in Tunisia. Under (NCS), SLN and  SYN clones, showed dry matter content 21%-45% higher compared to (RCS). Under (NCS), carotenoids were only detected in BDA and NMA at  levels higher compared to (RCS). However, the flavonoids content in SLN, ELD, SYN and BDA clones was 54-163% higher in (RCS) compared to  (NCS). HAA and LAA values were almost similar in both growing seasons except for Spunta and UNV which presented higher HAA values in (RCS)  and SLN which exhibited higher LAA values in (NCS). Therefore, the tubers issued from (NCS) revealed satisfying agronomic traits and functional  quality similar to (RCS) and suggest that (NCS) production will contribute to the balance of the demand/price of this agricultural produce.
Keywords: Highlands; potato; carotenoids; flavonoids; hydrophilic and lipophilic antioxidant activity; dry matter